Night-time and sleep in Asia and the West : exploring the dark side of life - Steger, Brigitte, 1965-; Brunt, Lodewijk, 1942- (Anthropology of Asia series., 2003)
Drawing together case studies from Asia and Europe, the reader can see the differences in cultural importance given to the night, and how the challenges and opportunities of modernity have been played out in the East and the West.